The Upper Cloth Revolt in South Travancore : Theological Interpretation of a Subaltern Movement - Wilson, Viju, (Brill | Manohar Publishers & Distributors, 2021)
In nineteenth century Travancore (Kerala), the lower caste women were not allowed to cover their upper body in public. This book is a study of the Nadars who protested and their movement which came to be known as the Upper Cloth Revolt, lasted from 1822 to 1859. It stands as a model movement for the subaltern communities in India. The exceptional stories of resistance and defiance against the dominant ruling class and castes, assertion of rights and liberative ventures opens up new horizons of hope for the communities who are still in the journey of their struggle and tells the subalterns to speak out against subjugation or they will remain powerless. In this revolt, religious faith worked as a source of liberation rather than a source of bondage. Recollecting and interpreting the subaltern history open new pathways of liberation and provide energy to claim new space in societal life.